Selective Catalysis Remedies Polysulfide Shuttling in Lithium‐Sulfur Batteries. Issue 38 (2nd August 2021) - Hua, Wuxing; Li, Huan; Pei, Chun; Xia, Jingyi; Sun, Yafei; Zhang, Chen; Lv, Wei; Tao, Ying; Jiao, Yan; Zhang, Bingsen; Qiao, Shi‐Zhang; Wan, Ying; et al.
Abstract: The shuttling of soluble lithium polysulfides between the electrodes leads to serious capacity fading and excess use of electrolyte, which severely bottlenecks practical use of Li‐S batteries. Here, selective catalysis is proposed as a fundamental remedy for the consecutive solid‐liquid‐solid sulfur redox reactions. The proof‐of‐concept Indium (In)‐based catalyst targetedly decelerates the solid‐liquid conversion, dissolution of elemental sulfur to polysulfides, while accelerates the liquid‐solid conversion, deposition of polysulfides into insoluble Li2 S, which basically reduces accumulation of polysulfides in electrolyte, finally inhibiting the shuttle effect. The selective catalysis is revealed, experimentally and theoretically, by changes of activation energies and kinetic currents, modified reaction pathway together with the probed dynamically changing catalyst (LiInS2 catalyst), and gradual deactivation of the In‐based catalyst. The In‐based battery works steadily over 1000 cycles at 4.0 C and yields an initial areal capacity up to 9.4 mAh cm −2 with a sulfur loading of ≈9.0 mg cm −2 . Abstract : Selective catalysis is proposed as a fundamental remedy for consecutive solid–liquid–solid sulfur redox reactions. This proof‐of‐concept In‐based catalyst targetedly decelerates the solid–liquid conversion, dissolution of elemental sulfur to polysulfides, while accelerating the liquid–solid conversion, deposition of polysulfides into insoluble Li2 S, which basically reduces accumulation of polysulfides in the electrolyte, finally inhibiting the shuttle effect in Li–S batteries.